Predicting apparent singlet oxygen quantum yields of dissolved black carbon and humic substances using spectroscopic indices. (March 2018) - Du, Ziyan; He, Yingsheng; Fan, Jianing; Fu, Heyun; Zheng, Shourong; Xu, Zhaoyi; Qu, Xiaolei; Kong, Ao; Zhu, Dongqiang
Abstract: Dissolved black carbon (DBC) is ubiquitous in aquatic systems, being an important subgroup of the dissolved organic matter (DOM) pool. Nevertheless, its aquatic photoactivity remains largely unknown. In this study, a range of spectroscopic indices of DBC and humic substance (HS) samples were determined using UV–Vis spectroscopy, fluorescence spectroscopy, and proton nuclear magnetic resonance. DBC can be readily differentiated from HS using spectroscopic indices. It has lower average molecular weight, but higher aromaticity and lignin content. The apparent singlet oxygen quantum yield (Φsinglet oxygen ) of DBC under simulated sunlight varies from 3.46% to 6.13%, significantly higher than HS, 1.26%–3.57%, suggesting that DBC is the more photoactive component in the DOM pool. Despite drastically different formation processes and structural properties, the Φsinglet oxygen of DBC and HS can be well predicted by the same simple linear regression models using optical indices including spectral slope coefficient ( S 275-295 ) and absorbance ratio ( E 2 / E 3 ) which are proxies for the abundance of singlet oxygen sensitizers and for the significance of intramolecular charge transfer interactions. The regression models can be potentially used to assess the photoactivity of DOM at large scales with in situ water spectrophotometry or satellite remote sensing. Graphical abstract: Highlights: Dissolved black carbon is one of the more photoactive components in the DOM pool. Dissolved black carbon has low average molecular weight but high lignin content. Correlations between the Φsinglet oxygen and optical indices of DOM are robust. The correlations can be well supported by the charge transfer model.